Local Government as Institutional Entrepreneur: Public–Private Collaborative Partnerships in Fostering Regional Entrepreneurship. (27th February 2018) - Xing, Yijun; Liu, Yipeng; Cooper, Sir Cary L.
Abstract: Due to the intertwined nature of private and public interests, local governments tend to use collaborative partnerships involving entrepreneurs to promote regional entrepreneurship. However, there is still a gap in the theory with regard to the mechanisms underpinning these collaborative partnerships. Drawing on the institutional entrepreneurship literature, we identify the enabling conditions and articulate the role played by local government as an institutional entrepreneur in fostering regional entrepreneurship through entrepreneurial public–private collaborative partnerships. This paper explicates two distinct mechanisms – the establishment of new institutional arrangements by the institutional entrepreneur and the advocation of diffusion by other actors – that underpin entrepreneurial public–private collaborative partnerships. Importantly, we underscore the crucial role played by returnee entrepreneurs who interact collaboratively with the institutional entrepreneur in affecting institutional change and fostering regional entrepreneurship. We conduct in‐depth qualitative interviews with local government officials, entrepreneurs and high‐tech park managers, in conjunction with performing content analysis of policy documents in a peripheral region of China – areas that have largely been neglected in scholarly research. This paper concludes with some theoretical and policy implications for public management and entrepreneurship.